State Imports: Theoretical Aspects Of The Peruvian Case, 1971-1976 - Boloña, Carlos (Universidad del Pacífico, 1978)
This work is the continuation of the research prepared by the Board of Cartagena Agreement entitled: “Public Sector’s Imports in Peru: 1971-1976”. Its objective is to update and develop the analytical aspect of State trading. It examines the approach of conventional economic theory and socialist economic theory to the subject and the study of the characteristics of the Peruvian case in the period 1971-1976. This is done with the aim to trace the foreign trade policies of the Peruvian State, with the purpose of counting with more elements of judgement for a global analysis of the subject.